2012
DOI: 10.1134/s1063074012010099
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids of the organs and tissues of echinoderms and tunicates from peter the great bay (Sea of Japan)

Abstract: 64Echinoderms and tunicates are classical objects of embryology, biochemistry, and molecular genetics, as well as food items and sources of promising biologi cally active substances [6].A great number of studies have been devoted to the phospholipid (PL) compositions of these animals, which are carried out, as a rule, on entire organisms. Studies that analyze the distribution of plasmalogen PL in marine invertebrates revealed the relationship between the level of organization of an animal and its plasmalogen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…In contrast to body wall, the spawns and intestines of Stichopus japonicus contained more classes of PL, as well as a lower content in PC but higher contents in almost all other PL classes (except for LPC). Actually, previous studies have also shown that PC (40.4-75.4% of the total PL), PE (11.5-34.2% of the total PL), PS (3.6-18.3% of the total PL) and PI (1.7-10.6% of the total PL) were the top four PL classes in sea cucumber Cucumaria frondosa japonica, Eupentacta fraudatrix, and Apostichopus japonicus (Kostetsky et al, 2012).…”
Section: Phospholipid Class Compositionmentioning
confidence: 88%
“…In contrast to body wall, the spawns and intestines of Stichopus japonicus contained more classes of PL, as well as a lower content in PC but higher contents in almost all other PL classes (except for LPC). Actually, previous studies have also shown that PC (40.4-75.4% of the total PL), PE (11.5-34.2% of the total PL), PS (3.6-18.3% of the total PL) and PI (1.7-10.6% of the total PL) were the top four PL classes in sea cucumber Cucumaria frondosa japonica, Eupentacta fraudatrix, and Apostichopus japonicus (Kostetsky et al, 2012).…”
Section: Phospholipid Class Compositionmentioning
confidence: 88%
“…No data is available in the literature on individual variation of the PL composition in sea stars and their organs, although some publications on comparative studies of the PL composition report the results that were obtained for total lipid extracts [8,10,11,24].…”
Section: Echinodermsmentioning
confidence: 98%
“…Data on phospholipid (PL) compositions for entire organ isms and individual organs have been published for decapods [7][8][9]17], sea stars [8,11,24,10], and ascidians [10,12,[18][19][20][21][22][23]. It is noteworthy that the cited studies were conducted on total lipid extracts that were obtained from a few specimens.…”
mentioning
confidence: 99%
“…Sea urchins are of great importance as sources of roe, the yield of which ranges from 6.0% to 20.0%, depending on their biological state [2]. Sea urchin roe has high food and biological value, and is rich in various biologically active substances [2][3][4], which display antioxidant effects [5,6], and antitumor [7,8], anti-inflammatory [9], geroprotective [10], antimicrobial [11] and other medicinal properties [12,13]. Due to this, a number of dietary supplements and pharmaceuticals recommended for the prevention and treatment of various pathological conditions of the human body have been developed on the basis of sea urchin roe [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The change in the quality of the urchin roe is due to the high activity of the enzymes found in it. Protein proteolysis, lipid hydrolysis and oxidation glycogen, phosphocreatine and ATP, and the formation of melanoidin pigments occur under their influence [4,16]. The structure and consistency of salted or frozen roe products are impaired within a short period of time; the flavour and colour characteristics change, and an unpleasant odour and bitter taste appear [17].…”
Section: Introductionmentioning
confidence: 99%